Good Governance in Bangladesh: A Study of World Governance Indicators - Mohammad Nur Ullah; Muhammad Sayadur Rahman (Indonesian Journal of Social Research (IJSR), 2021)
The inclusive philosophy of good governance is almost indispensable for the progress of state democracy in Bangladesh. However, the Bangladesh government is fighting a malicious virus in the governance structure that is visible in all sectors of the state. Against this backdrop, an attempt has been made to comprehend the general state of good governance in Bangladesh according to World Governance Indicators (WGI) of the World Bank. This study is based on mixed approach containing quantitative data from World Bank website (world economy.com) and qualitative data from existing literatures. The collected data have also been analyzed through table, chart and text. This paper found, the current situation in Bangladesh is appalling and detrimental to the socio-economic development of the country. This situation is crisscrossed by overpopulation, politicization, bureaucratization, corruption, poverty, broken law and order, and the narrow game of politics. This paper then outlines some of the policy guidelines needed to define good governance principles in Bangladesh. The results of this study are expected to be useful for policymakers in devising appropriate strategies to ensure good governance at all levels of government.